BRAF Fusion as Resistance Mechanism to Osimertinib in EGFR-Mutated NSCLC: A Case Report and Review of Literature - Marianna Peroni, MD; Alessandro Leonetti, MD, PhD; Roberta Minari, MSc, PhD; Michela Verzè, MSc; Letizia Gnetti, MD; Lorena Bottarelli, MSc, PhD; Cinzia Azzoni, MSc, PhD; Marco Galaverni, MD; Nicola Simoni, MD; Gabriele Missale, MD; Elisabetta Biasini, MD; Marcello Tiseo, MD, PhD (JTO Clinical and Research Reports)
Despite the efficacy of osimertinib in the first-line treatment of advanced EGFR-mutated NSCLC, the development of resistance is nearly inevitable. BRAF mutations and fusions are reported in 1% to 3% of patients with EGFR-mutated NSCLC receiving osimertinib and represent potential targetable alterations.In this case report, we discuss the rationale for EGFR-MEK co-inhibition in a patient with EGFR-mutated NSCLC treated with osimertinib that developed a CTNNA1-BRAF fusion at progression. In addition, we provide a brief overview of the current evidence of BRAF fusions as an acquired resistance mechanism to osimertinib and potential treatment strategies.